2010
DOI: 10.1037/a0018103
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes and children: The role of psychologists with families and communities.

Abstract: The 2008 Sichuan Province earthquake and 2005 Pakistan earthquake are examples of natural disasters that took an unimaginable toll on children. In such disaster management contexts, family members as well as health care and school personnel are the first-line responders and are natural sources of continued social support as children recover. Although psychologists have increasingly sophisticated understandings of post-disaster reactions and strategies for helping children and adolescents cope with trauma, mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 58 publications
(122 reference statements)
0
29
0
1
Order By: Relevance
“…This finding is inconsistent with the results of a previous study [35], which found that relocation predicted greater depression, although not traumatic stress. One possible explanation is that although relocation may initially change the survivors' social networks [35,57], it may reduce PTSD and depressive symptoms by limiting exposure to potential reminders of the disaster [15] and obtaining more material or emotional social support from local governments and organizations [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is inconsistent with the results of a previous study [35], which found that relocation predicted greater depression, although not traumatic stress. One possible explanation is that although relocation may initially change the survivors' social networks [35,57], it may reduce PTSD and depressive symptoms by limiting exposure to potential reminders of the disaster [15] and obtaining more material or emotional social support from local governments and organizations [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reviews of the research literature have summarized and identified a series of risk factors associated with the vulnerability to develop PTSD and depressive symptoms among child and adolescent survivors of natural disasters [13][14][15][16]. Among these risk factors, pre-existing child characteristics (e.g., gender, age, and prior exposure to traumatic events) have been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, depression among adolescents after earthquakes has attracted growing interest (e.g., Giannopoulou et al, 2006; Goenjian et al, 2011), because of the observed susceptibility of adolescents to trauma following natural disasters (e.g., Margolin et al, 2010). Prevalence rates for depression have ranged from 13.6 to 51.3% in adolescents exposed to earthquakes (e.g., Kolaitis et al, 2003; Fan et al, 2011; Qu et al, 2012; Ying et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Each child perceives and responds to such a traumatic experience in their own way, in other words, children are affected by earthquakes differently (Margolin, Ramos & Guran, 2010). Their reactions differ from each other; while some demonstrate behavioral changes, some others may pretend to ignore what has happened for days, weeks, and even months and finally come up with problem behaviours (Ergen 2009).…”
Section: Introductionmentioning
confidence: 98%